The microarchitectural variability in the echinoid skeleton: a 3D geometrical and stiffness characterization of Paracentrotus lividus - Valentina Perricone; Pasquale Cesarano; Mainak Deb; Derek Lublin; Mirko Mutalipassi; Lucia Pappalardo; David Kisailus; Francesco Marmo (Royal Society Open Science)
The sea urchin skeleton is a lightweight yet load-bearing hierarchical structure composed of calcitic plates with a species-specific three-dimensional (3D) trabecular meshwork known as stereom. Interestingly, the stereom architecture is extremely complex and variable in different basic types, each one characterized by a unique geometry and structural behaviours. The present study provides an in-depth analysis of the microarchitectural variability in the sea urchin Paracentrotus lividus. Accordingly, micro-CT scans, image analysis, 3D modelling, mean intercept length and linear elastic finite-element analysis were conducted to provide the first comprehensive insights on the structural variability of the different stereom types, their anisotropy and their mechanical behaviour calculated for tensile and shear loading. The findings demonstrate distinct structural adaptations, with anisotropic stereoms specializing in directional stress transfer and more isotropic stereoms facilitating a uniform stress distribution. These results provide critical insights into the mechanical functions of stereom variability and support bioinspired designs for lightweight and strong materials.